2014
DOI: 10.3945/jn.113.183186
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Supplementation Prevents Increases in Intestinal Permeability and Bacterial Translocation in Male Swiss Mice Subjected to Physical Exercise under Environmental Heat Stress

Abstract: Dietary supplementation with l-arginine has been shown to improve the intestinal barrier in many experimental models. This study investigated the effects of arginine supplementation on the intestinal permeability and bacterial translocation (BT) induced by prolonged physical exercise under heat stress. Under anesthesia, male Swiss mice (5-wk-old) were implanted with an abdominal sensor to record their core body temperature (T(core)). After recovering from surgery, the mice were divided into 3 groups: a non-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 53 publications
4
54
0
2
Order By: Relevance
“…Damage to the intestinal mucosa barrier will result in intestinal bacteria and endotoxin translocation, and further contribute to local and systemic inflammation and other complications. 16,30,31) BBR is a traditional herbal used to treat many gastrointestinal diseases worldwide. 2,3) Many studies have shown that BBR exhibits multiple pharmacological activities including antioxidant, anti-microbial, anti-tumor, and cholesterol-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the intestinal mucosa barrier will result in intestinal bacteria and endotoxin translocation, and further contribute to local and systemic inflammation and other complications. 16,30,31) BBR is a traditional herbal used to treat many gastrointestinal diseases worldwide. 2,3) Many studies have shown that BBR exhibits multiple pharmacological activities including antioxidant, anti-microbial, anti-tumor, and cholesterol-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the intestinal mucosa barrier will result in intestinal bacterial and endotoxin translocation and further contribute to local and systemic inflammations [4]. In clinical practice, patients with serious gastrointestinal failure undergoing open abdominal surgery often show systemic inflammatory syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…L-arginine has been shown to ameliorate intestinal epithelial barrier function by improving tight junctions 156 and to diminish luminal intestinal bacterial translocation following intestinal barrier impairment. [157][158][159] Recently, it has been shown that supplemental dietary L-arginine interacts with the intestinal microbiome to activate the immune system by enhancing intestinal Toll-like receptor signaling and the expression of secretory immunoglobulin A, mucins, and defensins. 160 Arginine given as oral supplementation is converted to ornithine and urea by the liver, the former being a precursor of polyamines (a known cell proliferative factor 161 ) by the activity of the ornithine decarboxylase enzyme.…”
Section: Effects Of Leaky Gut and Intestinal And Systemic Inflammatiomentioning
confidence: 99%